A new key generator algorithm based on sine map and SHA-3 for image encryption - Artuğer, Fırat; Özkaynak, Fatih (Springer, 2026)
In recent years, the need for secure cryptographic keys for various purposes has been constantly increasing. One of these areas is undoubtedly image encryption. In this study, a new key generation algorithm has been developed for use in image encryption algorithms. The proposed generator has a hybrid structure based on the chaotic sine map and the SHA-3 algorithm. It is aimed to produce strong keys by using the benefits of these two structures. To do this, first, bit sequences of the desired length are generated using the basic parameters of the sine map. Then, bit sequences of the same length are obtained using the SHA-3 algorithm. These two bit sequences are then subjected to an XOR operation to generate key values ??of the desired length. With this structure, 3 different bit sequences of 1 million length were produced. All of these bit sequences successfully passed NIST SP 800 ? 22 tests. This key value obtained in this study has been successfully applied to a new image encryption algorithm. The results of the study demonstrate that the proposed algorithm meets important cryptographic criteria such as information entropy, correlation-histogram analysis, NPCR, and UACI values. In addition, the simple and fast structure of the algorithm in key generation was the most important difference from other studies. © The Author(s) 2026.
Keywords: Image encryption; Key generator; RNG; SHA-3; Sine map